DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP IN UKRAINE UNDER MARTIAL LAW (Economic journal of Lesya Ukrainka Volyn National University, 2023)
There are many social problems in Ukraine, the number of which has only increased with the advent of war. Even after the end of hostilities, the number of victims will grow for a certain period, and jobs will become less. Unfortunately, the state, due to the difficult economic situation, will not be able to solve all the problems of socially vulnerable people. Therefore, it is necessary to look for new innovative approaches to solving acute social problems in order to avoid social crisis in Ukrainian society in the future. Social entrepreneurship is developing to some extent as a response to the current difficult economic situation. The use of business approaches in the social sphere is widespread in the world, in addition, it can become one of the main tools of social policy, removing a certain burden from it.The purpose of this research is to study the existing potential for the functioning and development of social entrepreneurship in Ukraine under martial law as a tool for solving existing social problems.The article investigates the development of social entrepreneurship in Ukraine, in particular, under martial law. The paper presents theoretical approaches to the definition of "social entrepreneurship", in particular, the most commonly used approaches: general, innovative, problem-oriented and mixed. A more complete interpretation of this category is proposed, covering each of the listed approaches.The main differences between social entrepreneurship and traditional business and charitable organization are presented. It is noted that today in Ukraine social entrepreneurship is not yet recognized in the legal field, but it functions quite successfully. The regional unevenness of the location of social enterprises is shown.The characteristic features of social entrepreneurship are highlighted and own criteria for defining social enterprises are proposed.The activities of social enterprises contribute to solving the problems of vulnerable segments of society, in particular their employment and social adaptation, this activity has a positive impact on the economic development of our country. Despite the existing support and opportunities for the development and functioning of social business in Ukraine, social entrepreneurship requires the creation of a legal framework that would clearly distinguish the activities of social enterprises from any other organizations and regulate their activities.
Keywords: social entrepreneurship, socially responsible business, socially vulnerable population, social effect, development of social entrepreneurship, martial law, social problem.